Indigenous Peoples’ stewardship of seagrass ecosystems - Federica Manca; Álvaro Fernández-Llamazares; Maricela De la Torre-Castro; Rachel Groom; Dana Lepofsky; Jordi F Pagès; David N Thomas; Mar Cabeza (Current Opinion in Environmental Sustainability, 2026)

Biotechnological potential of marine invertebrate-associated bacteria with antibacterial activity against aquaculture and human pathogens - Joicye Hernández-Zulueta; Lizeth N. Raygoza-Alcantar; Elizabeth Avila-Castro; Fabián A. Rodríguez-Zaragoza; Ignacio Cáceres; Jesús I. Delgado-Hernández; Michelle G. Bonilla-Urzúa (Brazilian Journal of Microbiology, 2026)

Tracking forest carbon and growth in large-scale passive restoration using multi-temporal airborne lidar - Felipe N. Begliomini; Fabian Jörg Fischer; Srinivasan Keshav; Pedro H.S. Brancalion; Paulo G. Molin; Angelica M. Almeyda Zambrano; Angélica Faria de Resende; Cassio Toledo; Catherine Torres de Almeida; Danilo Roberti Alves de Almeida; Davi Ernesto Alvarenga César; Eben N. Broadbent; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Simultaneous effusive and explosive activity in moderate-magnitude rhyolite eruptions: H2O and hydrogen isotopic investigation of the 1250 CE eruptions in Lipari, Sicily - Sebastian C. Walter; Jonathan M. Castro; Ilya N. Bindeman (Bulletin of Volcanology, 2026)
Three of the most recent rhyolite eruptions in Europe occurred approximately 800 years ago on the island of Lipari, Aeolian Islands, Sicily. These eruptions produced ash and lava deposits that share many of the physical and chemical traits known to exist in hybrid explosive-effusive silicic systems like the Mono Craters and Medicine Lake (USA), in addition to the recently active rhyolite volcanoes Chaitén (2008) and Cordón Caulle (2011), Chile. Here, we present a study on the microtextures, H 2 O concentrations, and δD values of pyroclastic and effusive deposits of three rhyolite eruptions on Lipari (Lami, Forgia Vecchia, and Rocche Rosse). Textural features of obsidian pyroclasts are, within our parameters of analysis, identical among the three centers. The three vents furthermore display overlapping bulk H 2 O concentrations (0.08–1.22 wt.%) that are in turn similar to previous studies on Lipari and other systems. Hydrogen isotope ratios (δD) decrease from −50.9 to −104.9 ‰ as magmatic water drops from 1.22 to 0.08 wt.%. Modeling of these geochemical trends implies that all erupted products degassed along a single coherent trend. This is consistent with a manner of eruption that would have involved simultaneous and repetitive explosive and effusive emission of isotopically heterogeneous gas from a single magma source. Collectively, our observations and analysis point to hybrid effusive-pyroclastic activity and support previous interpretations that Lipari’s three youngest rhyolitic centers were co-eruptive. This, in turn, implies that more than half of the island would have been affected by direct impacts of a single rhyolitic fissure event at ~ 1250 C E.

Microplastic in bivalves from the heavily contaminated Guanabara Bay, Rio de Janeiro, Brazil - Victor Vasques Ribeiro; Yonara Garcia; Caio César Achiles do Prado; Amanda Pereira Santos; Raimara S. Gomes; Andreia N. Fernandes; Ítalo Braga Castro (Environmental Research, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Growth of transformed Stevia rebaudiana in in vitro systems and the stimulation of steviol glycoside production with soy protein hydrolysates - Itzel Vianney Alvarado-Orea; Noelia Atilano-González; Enrique Villalobos-Amador; Julián Mario Peña-Castro; Paula N. Robledo-Narváez; Luis Alfredo Ortega-Clemente; David Paniagua-Vega; Ariana Arlene Huerta-Heredia (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Factors influencing small ruminant colostrum quality: A comprehensive review from 2020 to present - K. DiGiacomo; M. González-Cabrera; K. Capdevila Ospina; A. Argüello; F. Zamuner; N. Castro (Small Ruminant Research, 2026)

Combined Analysis of Gait Cycle and Imaging Parameters in Patients with Lumbar Disc Herniation: An Exploratory Study - Inês F. Mendes; Rita N. S. Fernandes; André P. G. Castro; Nuno A. R. Cristino (Annals of Biomedical Engineering, 2026)
This exploratory study investigates the association between imaging findings, clinical symptoms and gait parameters in patients with lumbar disc herniation (LDH). To explore this hypothesis, this study aims (1) to study how IVD height and intervertebral angle measurements obtained from MRI compare with those obtained from X-ray imaging; (2) to compare spatiotemporal gait parameters between LDH patients and healthy individuals and (3) to study if gait parameters vary in relation to clinical and imaging-derived measurements in LDH patients. Patients in this study underwent lumbar spine X-ray imaging and MRI, completed the Oswestry Disability Index (ODI) and Numerical Pain Rating Scale (NPRS) and participated in a gait analysis assessment. Measurements of IVD height and intervertebral angle revealed unexpected higher values in X-ray scans when compared to MRI, particularly in anterior IVD height and upper lumbar levels, providing important hints for the analysis of the initial imaging exam (usually X-ray scan). In addition, the analyzed gait parameters were altered in most LDH patients, with reduced walking speed, cadence, stride length and single support time and increased double support time, comparatively to healthy controls. A general tendency was found between intense radicular pain and high disability (NPRS and ODI scores, respectively) – both reflecting the impact of the clinical condition – and significant IVD pathology – evident on imaging – and altered gait parameters. However, some cases showed inconsistencies between clinical symptoms, imaging findings and gait parameters, suggesting that the relationship between the mentioned parameters is not always consistent. These findings underscore the importance of a multidimensional approach in evaluating LDH biomechanics, integrating clinical and gait parameters, while identifying potential discrepancies between imaging modalities for better initial assessment and follow-up.

Microplastics in a mosaic of Marine Protected Areas from southeastern Brazil: An assessment based on filter-feeding bivalves - Yonara Garcia; Victor Vasques Ribeiro; Caio César Achiles do Prado; Maria Teresa Castilho Mansor; Alexander Turra; Raimara S. Gomes; Andreia N. Fernandes; Ítalo Braga Castro (Marine Pollution Bulletin, 2026)

Deep learning for remote sensing mapping of roads, sidewalks, and bicycle lanes in Bogotá - Yang Shao; Justyn Kase Huckleberry; María Fernanda Ramírez-Bernal; Camilo Urbano-Castro; Christian Andrey Rincón-Acosta; Juan Camilo Aguirre-Salamanca; Yujie Wu; Gregory N. Taff; Jyot Chadha (Remote Sensing Applications: Society and Environment, 2026)

New findings of pseudotachylytes and their paleoseismic significance, Sierras Pampeanas of San Juan, Argentina - Gladis N. Palacio Balderramo; Brígida Castro de Machuca; Ana C. Mugas Lobos; Gustavo F. Ortíz; Gimena M. Bazán; Cristian E. Robledo (Journal of South American Earth Sciences, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Spatio-temporal performance of 2D local inertial hydrodynamic models for urban drainage and dam-break applications - Marcus N. Gomes Jr.; Maria A.R.A. Castro; Luis M.R. Castillo; Mateo H. Sánchez; Marcio H. Giacomoni; Rodrigo C.D. de Paiva; Paul D. Bates (Journal of Hydrology, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Seasonal variations in biofiltration efficiency of fish farm effluents using Ulva spp. - Cristina Rodríguez; N. L. Arroyo; M. C. Castro; A. Hernández de Rojas; X. Moreno-Ventas (Journal of Applied Phycology, 2026)
Intensive aquaculture generates nutrient-rich effluents that contribute to eutrophication if discharged untreated. Seaweed cultivation offers a sustainable approach to mitigate this impact while producing valuable biomass. This study evaluated the seasonal biofiltration efficiency and biomass production of Ulva spp. under simulated flatfish aquaculture effluent conditions using two experimental designs: parallel tanks and serial tanks with varying hydraulic retention times (HRTs). Ulva spp. showed higher nutrient removal and growth in summer compared to winter. In the parallel system, ammonium and phosphate removal exceeded 70% in summer but dropped below 50% in winter. In the serial system, nutrient removal peaked at a 24 h HRT, with ammonium and phosphate removal above 90%, while longer retention (36 h) did not improve performance. Biomass production followed a similar seasonal pattern, with higher yields in spring and summer. These results demonstrate that Ulva spp. are effective biofilters for aquaculture effluents, with performance strongly influenced by season and HRT. A two-tank serial configuration with 24 h HRT optimizes nutrient removal without compromising biomass production, providing useful insights for the design of sustainable seaweed-based biofiltration systems.

Glycerol-supplemented medium promotes transition of Cupriavidus necator from heterotrophic to lithoautotrophic growth - I. Castro Gonzalez; N. Gorret; L. Lauterbach; S. E. Guillouet (Biotechnology Letters, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Phylogenetic Relationships of the Moles and their Relatives (Talpidae): Insights from Mitogenomes - Sara Sampaio; André Gomes-dos-Santos; L. Filipe C. Castro; Jonathan J. Hughes; Ivan N. Bolotov; Viatcheslav V. Rozhnov; Marina V. Rutovskaya; Ilia G. Meschersky; Joana Paupério; Paulo C. Alves; Jeremy B. Searle; Manuel Lopes-Lima (Evolutionary Biology, 2025)

Exploring the determinants of bee diversity in tropical urban areas and their implications for conservation - Ingrid N. Gomes; Victor H.D. Silva; Rodrigo B. Gonçalves; Carlos A. Ordónez-Parra; Carolina P. Procópio-Santos; Sebastian O. Queroz; Diego M.P. Castro; João Carlos Pena; Pietro K. Maruyama (Landscape and Urban Planning, 2025)

How does the enhancement of carbon sequestration by non-native forests affect other ecosystem services? - Pilar Castro-Díez; Adrián Lázaro-Lobo; Romina D. Fernandez; Álvaro Alonso; Paula Cruces; Verónica Cruz-Alonso; Gary N. Ervin; Antonio Gallardo; Elena Granda; Daniel Gómez-Gras; Hélia Marchante; Daniel Moreno-Fernández; et al. (New Forests, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Antibacterial marinopyrroles and pseudilins act as protonophores - Chambers C. Hughes; Gabriel Castro-Falcón; Jan Straetener; Jan Bornikoel; Daniela Reimer; Trevor N. Purdy; Anne Berscheid; Florence M. Schempp; Dennis Y. Liu; Roger G. Linington; Heike Brötz-Oesterhelt (Phytochemistry Letters, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Telenutrition as a Solution to Dietitian Shortages in Rural Hospitals: A Pilot Implementation Study - N. Jouzi; M. Castro; C. Johnson (Journal of the Academy of Nutrition and Dietetics, 2025)

A case report about the detection of infectious hypodermal and hematopoietic necrosis virus (IHHNV) in shrimp displaying no clinical signs or histopathological lesions from farms on Colombia’s north coast - Jahnier A. Caicedo; Gersson M. Vásquez; Claudia P. Calderón; Eliana Celis; Jennifer-Natalie Castro; Joao Araujo-Junior; Hung N. Mai; Arun K. Dhar (Journal of Invertebrate Pathology, 2025)

Evaluation of resistance to charcoal rot in different phenological stages of the common bean crop - Jane C. S. Santos; Jerônimo C. Borel; Antonio E. S. Costa; Amanda N. Menezes; Mateus S. Castro; Kethelen G. S. Viana; Francine H. Ishikawa (European Journal of Plant Pathology, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

First report of biological contaminants in household water in the Philippines and long-term viability of Acanthamoeba species in one-year-old household water sediment - Frederick R. Masangkay; Rafaella Maxine N. Almeda; Alianna Louise M. Abustan; Sarah Veronica F. Almendrala; Jan Camille B. Bathan; Jowey Shekainah C. Belandres; Maria Allana Angela M. Buenaventura; Lea May F. Cabansag; Gemina Bienne V. Caralian; Mikhaella Denise V. Cueva; Leizette P. Cata-Al; Rance Leander H. Clemente; et al. (Science of The Total Environment, 2025)

Revisiting overland runoff modeling: Mixed flows and pseudo-kinematic waves - Oscar Castro-Orgaz; Juan V. Giraldez; Willi H. Hager; Francisco N. Cantero-Chinchilla (Advances in Water Resources, 2025)

Laboratory experiments on the visible to near- infrared (VNIR) spectroscopy of water ice and lunar highland simulant mixtures: Effects of particle size, particle shape, phase angle, and ice abundance - N. de Castro; S. Li (Icarus, 2025)

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Challenges for coral restoration in Southwestern Atlantic reefs: guidelines for ethical and sustainable practices - Miguel Mies; Guilherme O. Longo; Adalto Bianchini; Emiliano N. Calderon; Clovis B. Castro; Samuel C. Faria; Ronaldo B. Francini-Filho; Flávia M. Guebert; Marcelo V. Kitahara; Carlos H. F. Lacerda; Tito M. C. Lotufo; Laura F. B. Marangoni; et al. (Biodiversity and Conservation, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Exploring the impact of rainfall temporal distribution and critical durations on flood hazard modeling - Marcus N. Gomes; Vijay Jalihal; Maria Castro; Eduardo M. Mendiondo (Natural Hazards, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Valorization of residual ashes from boiler combustion process into activated carbon for adsorption of food industry wastewater - L. E. N. Castro; L. R. Matheus; W. G. Sganzerla; L. M. S. Colpini (International Journal of Environmental Science and Technology, 2025)

Bioactive arabinoxylan oligomers via colonic fermentation and enzymatic catalysis: Evidence of interaction with toll-like receptors from in vitro, in silico and functional analysis - Caroline de A. Guerreiro; Leandro A.D. Andrade; Cynthia Fernández-Lainez; Layanne N. Fraga; Gabriel López-Velázquez; Tatiana M. Marques; Samira B.R. Prado; Robert J. Brummer; João Roberto O. Nascimento; Victor Castro-Alves (Carbohydrate Polymers, 2025)

Recovery after exploitation of stalked barnacles is facilitated by the presence of conspecifics: a study of post-harvest gap recolonization dynamics in SW Europe - Víctor Gómez-del Campo; Julio Arrontes; Teresa Cruz; Elsa Vázquez; Gonzalo Macho; Eric Thiébaut; Katja Geiger; Joana N. Fernandes; David Jacinto; Alba Aguión; Teresa Silva; David Mateus; et al. (Reviews in Fish Biology and Fisheries, 2025)
We have followed the recovery of gaps produced either by harvesters or by scientists in stands of stalked barnacle ( Pollicipes pollicipes ) during two years in four regions of Europe (SW Portugal, Galicia and Asturias in Spain and Brittany in France; n = 423 gaps), which was extended to four years in Asturias (n = 252 gaps). The presence of adult conspecifics in the margins of the gaps increased by at least four times the probability of initiation of their recovery. After two years of follow-up in the four regions, 90% of the gaps with adjacent conspecifics had initiated recolonization as opposed to only 60% in gaps with no adjacent adults. These figures remained stable after three years of follow up in Asturias, pointing to a large fraction of gaps which are recalcitrant to recolonization. Once initiated, the median rate of recovery after latency was 0.47 cm 2 /month in the four regions and 0.61 cm 2 /month in Asturias, increasing from 0.5 to 2.5 cm 2 /month for a 0 to 25 cm increase of perimeter in contact with adults, which is consistent with heavy recruitment on the stalks of conspecifics. The median estimated time to full recovery of gaps which initiated recovery was 2.65 years, thus recolonization is a slow process. Our results point to the main recommendations that a barnacle clump should never be removed entirely, so that the remaining adults serve as recruitment nuclei for the population, and that a maximum scraper width of 3.5 cm should be set to limit accessory capture of non-target individuals.

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Comparative growth, survival, and feed conversion factor of the F1 generation of two new strains of tilapia Oreochromis niloticus produced by mass selection - Luis Daniel Espinosa-Chaurand; Rosa María Morelos-Castro; Ricardo García-Morales; Rodolfo Garza-Torres; Alejandro de Jesús Cortés-Sánchez; Alfonso N. Maeda-Martínez (Aquaculture, 2025)

Morphological and commercial quality variation of the stalked barnacle Pollicipes pollicipes: Patterns and drivers - A. Sousa; D. Jacinto; N. Penteado; D. Pereira; T. Silva; J.J. Castro; T. Cruz (Regional Studies in Marine Science, 2025)

Impact of common interest group participation and aquaculture development programs on fish productivity and net returns: evidence from Nile tilapia farming - Castro N. Gichuki; S. Wagura Ndiritu; Achom Barbara Emodoi (Aquaculture International, 2025)
Development programs have intensified support for the aquaculture sector to improve production and productivity, as well as food security and diet quality for smallholder farmers. This paper examines the impact of farmers’ participation in Common Interest Groups (CIGs) and the effects of aquaculture development support programs on the net returns and productivity of tilapia fish in Kenya. The study used household-level data of 506 members of the CIG who were randomly selected for the treatment group and benefited from Aquaculture Business Development Program (ABDP) interventions. The analysis employed an endogenous switching regression model to account for selection bias. The results reveal that membership in CIGs and receiving fish production interventions have resulted in a 32.3% increase in tilapia fish sales returns and a 6.6% increase in tilapia fish yields. Specifically, ABDP interventions are aimed at providing fish producers with ponds and cages had a significant and beneficial effect on fish yields and income returns. This finding suggests that policies with targeted interventions that support aquaculture infrastructure can play a significant role in increasing the incomes of smallholder farmers and reducing rural poverty in Kenya.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Polymorphic pseudogenes in the human genome - a comprehensive assessment - Mónica Lopes-Marques; M. João Peixoto; David N. Cooper; M. João Prata; Luísa Azevedo; L. Filipe C. Castro (Human Genetics, 2024)
Background: Over the past decade, variations of the coding portion of the human genome have become increasingly evident. In this study, we focus on polymorphic pseudogenes, a unique and relatively unexplored type of pseudogene whose inactivating mutations have not yet been fixed in the human genome at the global population level. Thus, polymorphic pseudogenes are characterized by the presence in the population of both coding alleles and non-coding alleles originating from Loss-of-Function (LoF) mutations. These alleles can be found both in heterozygosity and in homozygosity in different human populations and thus represent pseudogenes that have not yet been fixed in the population. Results: A methodical cross-population analysis of 232 polymorphic pseudogenes, including 35 new examples, reveals that human olfactory signalling, drug metabolism and immunity are among the systems most impacted by the variable presence of LoF variants at high frequencies. Within this dataset, a total of 179 genes presented polymorphic LoF variants in all analysed populations. Transcriptome and proteome analysis confirmed that although these genes may harbour LoF alleles, when the coding allele is present, the gene remains active and can play a functional role in various metabolic pathways, including drug/xenobiotic metabolism and immunity. The observation that many polymorphic pseudogenes are members of multigene families argues that genetic redundancy may play a key role in compensating for the inactivation of one paralogue. Conclusions: The distribution, expression and integration of cellular/biological networks in relation to human polymorphic pseudogenes, provide novel insights into the architecture of the human genome and the dynamics of gene gain and loss with likely functional impact.

Sediment recycling during the Holocene marine transgression in Ría de Vigo (NW Iberia): multiproxy evidence and environmental implications - C. Muñoz Sobrino; A. Castro-Parada; V. Cartelle; N. Martínez-Carreño; C. Delgado; N. Cazás; I. Lázaro; S. García-Gil (Quaternary Science Reviews, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Fangs and foliage: Unearthing the haemotoxic secrets of cannabis-dwelling rattlesnakes - Lachlan A. Bourke; Christina N. Zdenek; Tam M. Huynh; Wayne C. Hodgson; Alejandro Alagón; Edgar N. Castro; Jason Jones; Bryan G. Fry (Toxicon, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Organophosphate ester additives and microplastics in benthic compartments from the Loire estuary (French Atlantic coast) - J. Castro-Jiménez; Y. Aminot; N. Bely; C. Pollono; B.I.T. Idjaton; L. Bizzozero; O. Pierre-Duplessix; N.N. Phuong; J. Gasperi (Marine Pollution Bulletin, 2024)

An historical “wreck”: A transcriptome assembly of the naval shipworm, Teredo navalis Linnaeus, 1978 - André Gomes-dos-Santos; Marcos Domingues; Raquel Ruivo; Elza Fonseca; Elsa Froufe; Diana Deyanova; João N. Franco; L. Filipe C. Castro (Marine Genomics, 2024)

Synthesis of ultramicroporous zeolitic imidazolate framework ZIF-8 via solid state method using a minimum amount of deionized water for high greenhouse gas adsorption: A computational modeling - C.H. Belgacem; N. Missaoui; M.A.H. Khalafalla; G. Bouzid; H. Kahri; A.H. Bashal; A. Dhahri; L. Nouar; F.J. Melendez; M.E. Castro; H. Ghalla; Y. Zhou (Journal of Environmental Chemical Engineering, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Application of high-level Green–Naghdi theory to sill-controlled flows - Oscar Castro-Orgaz; Pedro P. Gamero-Ojeda; Francisco N. Cantero-Chinchilla; Tomás Morales de Luna; Hubert Chanson (Environmental Fluid Mechanics, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

PM chemical characterization at a semi-arid urban environment in Central Mexico - Dara Salcedo; Harry Alvarez-Ospina; Sara E. Olivares-Salazar; Rafael N. Liñan-Abanto; Telma Castro (Urban Climate, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Results from the Radiation Assessment Detector on the International Space Station: Part 3, combined results from the CPD and FND - C. Zeitlin; A.J. Castro; K.B. Beard; B.M. Hayes; M. Abdelmelek; D. Laramore; A.S. Johnson; N. Stoffle; R.F. Wimmer-Schweingruber; S. Löffler; R.R. Rios (Life Sciences in Space Research, 2023)

Results from the Radiation Assessment Detector on the International Space Station, Part 2: The fast neutron detector - C. Zeitlin; A.J. Castro; K.B. Beard; M. Abdelmelek; B.M. Hayes; A.S. Johnson; N. Stoffle; R.R. Rios; M.A. Leitgab; D.M. Hassler (Life Sciences in Space Research, 2023)

HERA: A Timepix-based radiation detection system for Exploration-class space missions - Nicholas N. Stoffle; Tom Campbell-Ricketts; Andrew Castro; Ramona Gaza; Cary Zeitlin; Stuart George; Mena Abdelmelek; Aaron Schram (Life Sciences in Space Research, 2023)

Results from the Radiation Assessment Detector on the International Space Station: Part 1, the Charged Particle Detector - C. Zeitlin; A.J. Castro; K.B. Beard; M. Abdelmelek; B.M. Hayes; A.S. Johnson; N. Stoffle; R.R. Rios (Life Sciences in Space Research, 2023)

Neuropathological and sociodemographic factors associated with the cortical amyloid load in aging and Alzheimer’s disease - Sayonara P. da Silva; Carla C. M. de Castro; Lívia N. Rabelo; Rovena C. Engelberth; Bernardino Fernández-Calvo; Felipe P. Fiuza (GeroScience, 2023)

A new method for extraction and pre-concentration of the heavy metals using a microemulsion system in winsor II equilibrium and determination by HR-CS AAS - Emily Cintia Tossi de A. Costa; Tereza N. de Castro Dantas; Djalma R. da Silva; Tatiane de A. Maranhão (Chemosphere, 2023)

Whose values count? A review of the nature valuation studies with a focus on justice - M Schaafsma; S Ahn; AJ Castro; N Dendoncker; A Filyushkina; D González-Jiménez; Mariaelena Huambachano; N Mukherjee; TH Mwampamba; J Ngouhouo-Poufoun; I Palomo; R Pandit; et al. (Current Opinion in Environmental Sustainability, 2023)

P19-01: Prenatal exposure to mixtures of potentially toxic and essential metals decreased DNA repair capacity in newborns from a polluted area - M. Paz-Sabillón; N. Montes-Castro; L.M. Del Razo; L. Torres-Sánchez; B. Quintanilla-Vega (Toxicology Letters, 2023)

P03-24: Impact of cadmium on cell viability and migration of human lung cells in vitro - D.C. Carreira; R. Manguinhas; R.B. Soares; N. Gil; M. Castro; J.P. Miranda; N.G. Oliveira (Toxicology Letters, 2023)

Variational RANS modeling of hydraulic jumps - Oscar Castro-Orgaz; Pedro P. Gamero-Ojeda; Francisco N. Cantero-Chinchilla; Tomás Morales de Luna; Willi H. Hager; Fabián A. Bombardelli (Ocean Engineering, 2023)

Rajids ovipositing on marine litter: A potential threat to their survival - Miguel Valderrama-Herrera; Sara Amada Cardenas; Carlos Calvo-Mac; Renzo Gustavo Celi-Vértiz; Valeria Liz Chumpitaz-Levano; Walter Eduardo Flores-Miranda; Zoila M.T. Lopez-Tirado; Mariana Molina-Alvarez; Diana N. Rubio-Cheon; Maryalejandra Trucios-Castro; Melisa D. Fernández Severini; Ana D. Forero López; et al. (Marine Pollution Bulletin, 2023)

Effect of cytobrush technique in mares - Jackson F Gille; Polyanna N da Silva; Thadeu Castro (Journal of Equine Veterinary Science, 2023)

Reproductive performance of hair ewes and rams implanted with melatonin previous to the anestrus season in northwest Mexico - José C. Leyva-Corona; Norberto I. Angulo-Valenzuela; Blanca M. Laborin-Escalante; Miguel A. Gastelum-Delgado; N. Jahzeel Silva-Avila; Pablo Luna-Nevárez; Carlos E. Aragón-López; Miguel A. Sánchez-Castro; Marcela I. Morales-Pablos (Tropical Animal Health and Production, 2023)

Sigma mapping for drainage problems with a time-dependent water table - Oscar Castro-Orgaz; Francisco N. Cantero-Chinchilla; Juan V. Giraldez; Willi H. Hager (Advances in Water Resources, 2023)

Assessment of eutrophication from phosphorus remobilization after resuspension of coastal sediments from an urban tropical estuary - Christiane do N. Monte; Ana Paula de Castro Rodrigues; Matheus Cavalcante Silva; Luana J. S. Ferreira; Gustavo Monte; Carla Semiramis Silveira; Renato Campello Cordeiro; Wilson Machado (Environmental Science and Pollution Research, 2023)

Oxidative potential of ambient PM2.5 from São Paulo, Brazil: Variations, associations with chemical components and source apportionment - Eleni Serafeim; Athanasios Besis; Athanasios Kouras; Camila N. Farias; Aleinnys B. Yera; Guilherme M. Pereira; Constantini Samara; Pérola de Castro Vasconcellos (Atmospheric Environment, 2023)

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Inter-annual variability of land surface fluxes across vineyards: the role of climate, phenology, and irrigation management - N. Bambach; W. Kustas; J. Alfieri; F. Gao; J. Prueger; L. Hipps; L. McKee; S. J. Castro; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Irrigation and other agricultural management practices play a key role in land surface fluxes and their interactions with atmospheric processes. California’s Central Valley agricultural productivity is strongly linked to water availability associated with conveyance infrastructure and groundwater, but greater scrutiny over agricultural water use requires better practices particularly during extended and severe drought conditions. The future of irrigated agriculture in California is expected to be characterized neither by perpetual scarcity nor by widespread abundance. Thus, further advancing irrigation technologies and improving management practices will be key for California’s agriculture sustainability. In this study, we present micrometeorological observations from the Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project. Daily, seasonal, and inter-seasonal surface flux patterns and relationships across five vineyards over three distinct California wine production regions were investigated. Vineyard actual evapotranspiration showed significant differences at the sub-daily and daily scale when comparisons across wine production regions and varieties were performed. Water use in vineyards in the Central Valley was about 70% greater in comparison to the vineyards at the North Coast area due to canopy size, atmospheric demand, and irrigation inputs. Inter-annual variability of surface fluxes was also significant, even though, overall weather conditions (i.e., air temperature, vapor pressure deficit, wind speed, and solar radiation) were not significantly different. Thus, not only irrigation but also other management practices played a key role in seasonal water use, and given these differences, we conclude that further advancing ground-based techniques to quantify crop water use at an operational scale will be key to facing California’s agriculture present and future water challenges.

Evapotranspiration uncertainty at micrometeorological scales: the impact of the eddy covariance energy imbalance and correction methods - N. Bambach; W. Kustas; J. Alfieri; J. Prueger; L. Hipps; L. McKee; S. J. Castro; J. Volk; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Under ideal conditions, evapotranspiration ( ET ) fluxes derived through the eddy covariance (EC) technique are considered a direct measure of actual ET . Eddy covariance flux measurements provide estimates at a temporal frequency that allows examining sub-daily, daily, and seasonal scale processes and relationships between different surface fluxes. The Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project has collected micrometeorological and biophysical data to ground-truth new remote sensing tools for fine-tuning vineyard irrigation management across numerous sites since 2013. This rich dataset allows us to quantify the impact of different approaches to estimate daily ET fluxes, while accounting for energy imbalance. This imbalance results from the lack of agreement between the total available energy and turbulent fluxes derived by the EC technique. We found that different approaches to deal with this energy imbalance can lead to uncertainty in daily ET estimates of up to 50%. Over the growing season, this uncertainty can lead to considerable biases in crop water use estimates, which in some cases were equivalent to ~ 1/3rd of the total growing season applied irrigation We analyzed ET uncertainty relative to atmospheric meteorological, stability, and advective conditions, and highlight the importance of recognizing limitations of micrometeorological observational techniques, considered state of the art, to quantify ET for model validation and field-scale monitoring. This study provides a framework to quantify daily ET estimates’ uncertainty and expected reliability when using the eddy covariance technique for ground-truthing or model validation purposes.

Shallow fluid flow over an obstacle: higher-order non-hydrostatic modeling and breaking waves - Oscar Castro-Orgaz; Francisco N. Cantero-Chinchilla; Hubert Chanson (Environmental Fluid Mechanics, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Predicting in vitro fertilization success in the Brazilian public health system: a machine learning approach - Nayara C. N. Barreto; Giulia Z. Castro; Ramon G. Pereira; Francisco A. N. Pereira; Fernando M. Reis; Wagner M. Junior; Ines K. D. Cavallo; Karina B. Gomes (Medical & Biological Engineering & Computing, 2022)

Diversity, distribution, and environmental drivers of coralline red algae: the major reef builders in the Southwestern Atlantic - Marina Nasri Sissini; Gabrielle Koerich; Maria Beatriz de Barros-Barreto; Luana M. Coutinho; Fernanda P. Gomes; William Oliveira; Iara O. Costa; José Marcos de Castro Nunes; Maria Carolina Henriques; Talita Vieira-Pinto; Beatriz N. Torrano-Silva; Mariana Cabral Oliveira; et al. (Coral Reefs, 2022)

A large-scale comparison of reproduction and recruitment of the stalked barnacle Pollicipes pollicipes across Europe - Alba Aguión; Teresa Cruz; José Luis Acuña; Caroline Broudin; João J. Castro; Dominique Davoult; Jesus Dubert; Joana N. Fernandes; Katja J. Geiger; David Jacinto; David Mateus; Carlota Muñiz; et al. (Marine Biology, 2022)
Understanding large-scale spatial and temporal patterns of marine populations is a central goal in ecology, which has received renewed attention under climate change. However, few studies explore the large-scale dynamics of populations using standardized protocols and during the same time frames. We studied the phenology and intensity of reproduction and recruitment for the intertidal stalked barnacle Pollicipes pollicipes over an European scale and described their potential linkages with environmental variables. This species supports profitable fisheries in the Iberian Peninsula (Spain and Portugal). In Brittany (France), we had observed a significant lower reproductive effort (long non-breeding season, short breeding period in summer) and low values of recruitment intensity. This pattern may be related to the fact that Brittany corresponds to the northern limit of the distribution of this species in continental Europe. On the Iberian Peninsula, the most different region was Galicia (Spain), with Asturias (Spain) and SW Portugal being more similar. In Galicia, we have observed a contradictory pattern characterized by the absence of a non-breeding period and by a shorter recruitment season than observed in other Iberian regions. Our results suggest that air temperature, SST and chlorophyll-a might be related to the variability in reproduction and recruitment patterns of P. pollicipes . Moreover, spring and early summer upwelling in SW Portugal and Galicia might be inhibiting recruitment in this period. At the northern limit, the expected increase in performance under climate change might facilitate the recovery of populations after exploitation, increasing the resilience of the resource to fishing pressure.

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Ambio fit for the 2020s - Erik Andersson; Wiebren J. Boonstra; Maricela de la Torre Castro; Alice C. Hughes; Ulrik Ilstedt; Arne Jernelöv; Bengt-Gunnar Jonsson; Zahra Kalantari; Carina Keskitalo; Emma Kritzberg; Thomas Kätterer; Jeffrey A. McNeely; et al. (Ambio, 2022)

Nanotechnology-Driven Cell-Based Therapies in Regenerative Medicine - D. Alzate-Correa; W. R. Lawrence; A. Salazar-Puerta; N. Higuita-Castro; D. Gallego-Perez (The AAPS Journal, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Determination of Fipronil and Fipronil-Sulfone in Surface Waters of the Guandu River Basin by High-Performance Liquid Chromatography with Mass Spectrometry - Thais P. Ferreira; Glauco F. Bauerfeldt; Rosane N. Castro; Viviane S. Magalhães; Melina C. C. Alves; Fábio B. Scott; Yara P. Cid (Bulletin of Environmental Contamination and Toxicology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

BoaγPLI from Boa constrictor Blood is a Broad-Spectrum Inhibitor of Venom PLA2 Pathophysiological Actions - Caroline Fabri Bittencourt Rodrigues; Christina N. Zdenek; Caroline Serino-Silva; Karen de Morais-Zani; Kathleen Fernandes Grego; Melisa Bénard-Valle; Edgar Neri-Castro; Alejandro Alagón; Anita Mitico Tanaka-Azevedo; Bryan Grieg Fry (Journal of Chemical Ecology, 2021)

Activation of C–C motif chemokine receptor 2 modulates testicular macrophages number, steroidogenesis, and spermatogenesis progression - A. F. A. Figueiredo; N. T. Wnuk; C. P. Vieira; M. F. F. Gonçalves; M. R. G. Brener; A. B. Diniz; M. M. Antunes; H. M. Castro-Oliveira; G. B. Menezes; G. M. J. Costa (Cell and Tissue Research, 2021)

Adenosine A2A receptor null chondrocyte transcriptome resembles that of human osteoarthritic chondrocytes - Cristina M. Castro; Carmen Corciulo; Benjamin Friedman; Zhi Li; Samson Jacob; David Fenyo; Bruce N. Cronstein (Purinergic Signalling, 2021)

Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - T. Bento dos Santos; J. F. Rodrigues; P. Castro; B. Cotrim; I. Pereira; J. A. Ferreira; C. Meireles; N. Ferreira; P. Ferreira; A. Ribeiro; F. Guimarães (International Journal of Earth Sciences, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Miconia albicans and Curcuma longa herbal medicines positively modulate joint pain, function and inflammation in patients with osteoarthritis: a clinical study - Thiago P. O. Gomes; Jonathan I. N. Souza; Lucas C. Somerlate; Vanessa A. Mendonça; Nerilson M. Lima; Gabriela P. Carli; Sandra B. R. Castro; Teresinha de Jesus A. S. Andrade; João V. L. Dias; Marcone A. L. Oliveira; Caio C. S. Alves; Alessandra P. Carli (Inflammopharmacology, 2021)

Correction to: Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

First report of meticillin-resistant Staphylococcus aureus harboring mecC gene in milk samples from cows with mastitis in southeastern Brazil - Maria de Fatima N. F. Alves; Bruno Penna; Renata F. A. Pereira; Reinaldo B Geraldo; Evelize Folly; Helena Carla Castro; Fabio Aguiar-Alves (Brazilian Journal of Microbiology, 2020)

Insights on Zika virus envelope gene conservation in American outbreaks - Mateus V. Thomazella; Quirino A. Lima Neto; Francisco F. Duarte Junior; Fernando A. Jorge; Déborah de Castro Moreira; Amauri D. Leal Junior; Mayra M. Presibella; Irina N. Riediger; Rafael A. da Silva; Isabel Maria V. G. de Carvalho; Dennis A. Bertolini (Brazilian Journal of Microbiology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Delinted cottonseed in diets for finishing sheep - W. J. R. Castro; A. M. Zanine; D. J. Ferreira; A. L. Souza; R. M. A. Pinho; M. O. M. Parente; H. N. Parente; E. M. Santos (Tropical Animal Health and Production, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

The use of an Allonais inaequalis reproduction test as an ecotoxicological bioassay - M. C. Felipe; A. C. Bernegossi; G. B. Castro; F. R. Pinheiro; B. L. Nadai; B. N. Cardoso-Silva; J. J. Corbi (Ecotoxicology, 2020)

Magnetic biomonitoring of atmospheric dust using tree leaves of Ficus benjamina in Querétaro (México) - Ana G. Castañeda-Miranda; Marcos A. E. Chaparro; Adolfo Pacheco-Castro; Mauro A. E. Chaparro; Harald N. Böhnel (Environmental Monitoring and Assessment, 2020)

Detection of fluid mud layers using tuning fork, dual-frequency echo sounder, and chirp sub-bottom measurements - Juliane Castro Carneiro; Marcos N. Gallo; Susana B. Vinzón (Ocean Dynamics, 2020)

Non-linear shallow water flow modelling over topography with depth-averaged potential equations - Oscar Castro-Orgaz; Francisco N. Cantero-Chinchilla (Environmental Fluid Mechanics, 2020)

Mangifera indica L. as Airborne Metal Biomonitor for Regions of the State of Espírito Santo (Brazil) - Leonardo Z. de Castro; Thaís R. B. da Silva; Silas N. Ronchi; Adriana A. T. Guimarães; Hermínio A. Nalini Júnior; Juliano S. Ribeiro; Silvia C. G. Coutinho; Elisangela F. Pimentel; Denise C. Endringer (Water, Air, & Soil Pollution, 2020)

Removal of Zn and Cd from Overlying Water by Mangrove Sediments: Testing the Effects of Sediment Resuspension/Redeposition Events - K. N. Suzuki; R. J. M. Castro; M. N. Sondermann; E. C. Machado; A. B. Bellido; R. T. Lopes; W. Machado (Water, Air, & Soil Pollution, 2020)

Molecular evidence for three genetic species of Dipteryx in the Peruvian Amazon - Carmen Garcia-Davila; David Aldana Gomero; Jean-François Renno; Rossana Diaz Soria; Gabriel Hidalgo Pizango; Gerardo Flores Llampazo; Diana Castro-Ruiz; Eduardo Mejia de Loayza; Carlos Angulo Chavez; Malte Mader; Niklas Tysklind; Kathelyn Paredes-Villanueva; et al. (Genetica, 2020)

Optical properties of atmospheric particles over an urban site in Mexico City and a peri-urban site in Queretaro - Rafael N. Liñán-Abanto; O. Peralta; D. Salcedo; L. G. Ruiz-Suárez; P. Arnott; G. Paredes-Miranda; H. Alvarez-Ospina; T. Castro (Journal of Atmospheric Chemistry, 2019)

Using Large-Eddy Simulation and Wind-Tunnel Data to Investigate Peak-to-Mean Concentration Ratios in an Urban Environment - J. M. Santos; N. C. Reis; I. P. Castro; E. V. Goulart; Z. T. Xie (Boundary-Layer Meteorology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

Effects of alternative silvicultural systems on litter decomposition and nutrients dynamics in sub-Antarctic forests - N. Oro Castro; A. Moretto; L. J. Selzer; J. Escobar (Agroforestry Systems, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Reproductive dynamics of the white shrimp Litopenaeus schmitti (Burkenroad 1936) in a beach seine fishery in northeastern Brazil - Cecília Craveiro; Silvio Peixoto; Emanuell F. Silva; Leandro N. Eduardo; Alex S. Lira; Hildemário Castro-Neto; Flávia L. Frédou; Roberta Soares (Invertebrate Reproduction & Development, 2019)

Correlation between geometric parameters of the left coronary artery and hemodynamic descriptors of atherosclerosis: FSI and statistical study - N. Pinho; C. F. Castro; C. C. António; N. Bettencourt; L. C. Sousa; S. I. S. Pinto (Medical & Biological Engineering & Computing, 2019)

Immunological MHC supertypes and allelic expression: how low is the functional MHC diversity in free-ranging Namibian cheetahs? - N. Schwensow; A. Castro-Prieto; B. Wachter; S. Sommer (Conservation Genetics, 2019)

The PERCEBES project: science for the spatial management of the stalked barnacle fishery in the Atlantic Arc - Katja Geiger; José Luis Acuña; Alba Aguión; Arrontes Julio; Marion Ballenghiem; Yaisel J. Borrell; Caroline Broudin; João Castro; Juliette Chiss; Teresa Cruz; Dominique Davoult; Jesus Dubert; et al. (Frontiers in Marine Science, 2019)

Characterization and Comparison of Genetic Variation in Cotesia flavipes (Hymenoptera: Braconidae) Mass Reared for Biological Pest Control Using Microsatellite Markers - F C Freitas; A C Morales-Corrêa e Castro; N C C P Barbosa; O A Fernandes (Neotropical Entomology, 2018)

Comparison of Health Communication Channels for Reaching Hispanics About Biobanking: a Pilot Trial - Jessica McIntyre; Julio Jiménez; Yonaira M. Rivera; Steven K. Sutton; Gloria Asencio; Eida M. Castro-Figueroa; Clement K. Gwede; Thomas H. Brandon; Susan T. Vadaparampil; Vani N. Simmons; Johanna Corchado; Laura Moreno; et al. (Journal of Cancer Education, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

First evidence of viral and bacterial oyster pathogens in the Brazilian coast - D F Mello; N M Danielli; F Curbani; V A Pontinha; S Suhnel; M A M Castro; S C Medeiros; N C Wendt; R Trevisan; A R M Magalhães; A L Dafre (Journal of Fish Diseases, 2018)

Bleaching in reef invertebrate larvae associated with Symbiodinium strains within clades A–F - M. Mies; A. Z. Güth; C. B. Castro; D. O. Pires; E. N. Calderon; M. Pompeu; P. Y. G. Sumida (Marine Biology, 2018)

Production of three symbiosis-related fatty acids by Symbiodinium types in clades A–F associated with marine invertebrate larvae - M. Mies; A. B. Chaves-Filho; S. Miyamoto; A. Z. Güth; A. A. Tenório; C. B. Castro; D. O. Pires; E. N. Calderon; P. Y. G. Sumida (Coral Reefs, 2017)

Plume composition and volatile flux of Nyamulagira volcano, Democratic Republic of Congo, during birth and evolution of the lava lake, 2014–2015 - N. Bobrowski; G. B. Giuffrida; S. Arellano; M. Yalire; M. Liotta; L. Brusca; S. Calabrese; S. Scaglione; J. Rüdiger; J. M. Castro; B. Galle; D. Tedesco (Bulletin of Volcanology, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

Asparagus macrorrhizus Pedrol, Regalado et López-Encina, an endemic species from Spain in extreme extinction risk, is a valuable genetic resource for asparagus breeding - J. J. Regalado; R. Moreno; P. Castro; E. Carmona-Martin; R. Rodríguez; J. Pedrol; N. Larrañaga; R. Guillén; J. Gil; C. L. Encina (Genetic Resources and Crop Evolution, 2017)

Woody plant community structure in “Dense Cerrado” fragments in the Upper Basin of the Araguaia River (Central Brazil): relationship with habitat loss and geographical distance - Mariana N. Siqueira; Selma Simões de Castro; Alessandro R. Morais; Karla M. S. Faria (Brazilian Journal of Botany, 2017)

The role of epigenetic modifiers in extended cultures of functional hepatocyte-like cells derived from human neonatal mesenchymal stem cells - M. Cipriano; J. C. Correia; S. P. Camões; N. G. Oliveira; P. Cruz; H. Cruz; M. Castro; J. L. Ruas; J. M. Santos; J. P. Miranda (Archives of Toxicology, 2017)

RA Differentiation Enhances Dopaminergic Features, Changes Redox Parameters, and Increases Dopamine Transporter Dependency in 6-Hydroxydopamine-Induced Neurotoxicity in SH-SY5Y Cells - Fernanda M. Lopes; Leonardo Lisbôa da Motta; Marco A. De Bastiani; Bianca Pfaffenseller; Bianca W. Aguiar; Luiz F. de Souza; Geancarlo Zanatta; Daiani M. Vargas; Patrícia Schönhofen; Giovana F. Londero; Liana M. de Medeiros; Valder N. Freire; et al. (Neurotoxicity Research, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

Reliable methods for determination of triazine herbicides and their degradation products in seawater and marine sediments using liquid chromatography-tandem mass spectrometry - N. Rodríguez-González; R. Uzal-Varela; M.J. González-Castro; S. Muniategui-Lorenzo; E. Beceiro-González (Environmental Science and Pollution Research, 2017)

Identification and genetic characterization of classical swine fever virus isolates in Brazil: a new subgenotype - Marta N. F. Silva; Diogo M. F. Silva; Adriana S. Leite; Ana L. V. Gomes; Antonio C. Freitas; Jose W. Pinheiro-Junior; Roberto S. Castro; Andre L. S. Jesus (Archives of Virology, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Synthesis and in vitro evaluation of novel triazole/azide chalcones - Fernanda C. G. Evangelista; Maralice O. Bandeira; Graziele D. Silva; Marina G. Silva; Silmara N. Andrade; Deisielly R. Marques; Luciana M. Silva; Whocely V. Castro; Fabio V. Santos; Gustavo H. R. Viana; José A. F. P. Villar; Adriano P. Sabino; et al. (Medicinal Chemistry Research, 2017)

Diabetes and breast cancer mortality in Black women - Marjory Charlot; Nelsy Castro-Webb; Traci N. Bethea; Kimberly Bertrand; Deborah A. Boggs; Gerald V. Denis; Lucile L. Adams-Campbell; Lynn Rosenberg; Julie R. Palmer (Cancer Causes & Control, 2017)

Simvastatin Treatment Modulates Mechanically-Induced Injury and Inflammation in Respiratory Epithelial Cells - N. Higuita-Castro; V. C. Shukla; C. Mihai; S. N. Ghadiali (Annals of Biomedical Engineering, 2016)

Acute hypoxia up-regulates HIF-1α and VEGF mRNA levels in Amazon hypoxia-tolerant Oscar (Astronotus ocellatus) - R. B. Baptista; N. Souza-Castro; V. M. F. Almeida-Val (Fish Physiology and Biochemistry, 2016)

Radial and tangential migration of telencephalic somatostatin neurons originated from the mouse diagonal area - Luis Puelles; N. Morales-Delgado; P. Merchán; B. Castro-Robles; M. Martínez-de-la-Torre; C. Díaz; J. L. Ferran (Brain Structure and Function, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

Antinociceptive effect of a novel armed spider peptide Tx3-5 in pathological pain models in mice - Sara M. Oliveira; Cássia R. Silva; Gabriela Trevisan; Jardel G. Villarinho; Marta N. Cordeiro; Michael Richardson; Márcia H. Borges; Célio J. Castro; Marcus V. Gomez; Juliano Ferreira (Pflügers Archiv - European Journal of Physiology, 2016)

Insights into the virulence‐related genes of Edwardsiella tarda isolated from turbot in Europe: genetic homogeneity and evidence for vibrioferrin production - N Castro; C R Osorio; N Buján; J C Fuentes; J Rodríguez; M Romero; C Jiménez; A E Toranzo; B Magariños (Journal of Fish Diseases, 2016)
Edwardsiella tarda has long been known as a pathogen that causes severe economic losses in aquaculture industry. Insights gained on E. tarda pathogenesis may prove useful in the development of new methods for the treatment of infections as well as preventive measures against future outbreaks. In this report, we have established the correlation between the presence of virulence genes, related with three aspects typically involved in bacterial pathogenesis (chondroitinase activity, quorum sensing and siderophore‐mediated ferric uptake systems), in the genome of E. tarda strains isolated from turbot in Europe and their phenotypic traits. A total of 8 genes were tested by PCR for their presence in 73 E. tarda isolates. High homogeneity was observed in the presence/absence pattern of all the strains. Positive results in the amplification of virulence‐related genes were correlated with the detection of chondroitinase activity in agar plates, in vivo AHL production during fish infection and determination of type of siderophore produced by E. tarda . To the best of our knowledge, this is the first study carried out with European strains on potential virulence factors. Furthermore, we demonstrated for the first time that E. tarda produces the siderophore vibrioferrin.

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Acceptability and Cultural Appropriateness of Self-Help Booklets for Relapse Prevention in Puerto Rico - Nicole S. Menzie; Vani N. Simmons; Gwendolyn P. Quinn; Diana B. Diaz; Barbara Piñeiro; Julio Jimenez; Eida Castro; Thomas H. Brandon (Journal of Cancer Education, 2015)

HER2 and β-catenin protein location: importance in the prognosis of breast cancer patients and their correlation when breast cancer cells suffer stressful situations - F. Darío Cuello-Carrión; Jorge E. Shortrede; Daiana Alvarez-Olmedo; Niubys Cayado-Gutiérrez; Gisela N. Castro; Felipe C. M. Zoppino; Martín Guerrero; Estefania Martinis; Rodolfo Wuilloud; Nidia N. Gómez; Verónica Biaggio; Javier Orozco; et al. (Clinical & Experimental Metastasis, 2015)

Concentrations of persistent organic pollutants (POPs) and heavy metals in soil from San Luis Potosí, México - Francisco Javier Perez-Vazquez; Rogelio Flores-Ramirez; Angeles Catalina Ochoa-Martinez; Sandra Teresa Orta-Garcia; Berenice Hernandez-Castro; Leticia Carrizalez-Yañez; Iván N. Pérez-Maldonado (Environmental Monitoring and Assessment, 2015)

An environmentally friendly method for the determination of triazine herbicides in estuarine seawater samples by dispersive liquid–liquid microextraction - N. Rodríguez-González; E. Beceiro-González; M. J. González-Castro; S. Muniategui-Lorenzo (Environmental Science and Pollution Research, 2015)

Predicting climate change impacts on native and invasive tree species using radial growth and twenty-first century climate scenarios - N. González-Muñoz; J. C. Linares; P. Castro-Díez; U. Sass-Klaassen (European Journal of Forest Research, 2014)

Technical Evaluation of Glauconies as Alternative Potassium Fertilizer from the Salamanca Formation, Patagonia, Southwest Argentina - Corina Franzosi; Liliana N. Castro; Ana María Celeda (Natural Resources Research, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Irrigation water quality and the benefits of implementing good agricultural practices during tomato (Lycopersicum esculentum) production - M. Estrada-Acosta; M. Jiménez; C. Chaidez; J. León-Félix; N. Castro-del Campo (Environmental Monitoring and Assessment, 2014)

Flow cytometry analysis of cell population dynamics and cell cycle during HIV-1 envelope-mediated formation of syncytia in vitro - Israel Torres-Castro; César N. Cortés-Rubio; Guadalupe Sandoval; Edmundo Lamoyi; Carlos Larralde; Leonor Huerta (In Vitro Cellular & Developmental Biology - Animal, 2014)

Acquisition of resistant microorganisms and infections in HIV-infected patients admitted to the ICU - N. Cobos-Trigueros; M. Rinaudo; M. Solé; P. Castro; J. Pumarol; C. Hernández; S. Fernández; J. M. Nicolás; J. Mallolas; J. Vila; L. Morata; J. M. Gatell; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Lack of superiority of invasive over co-occurring native riparian tree seedling species - N. González-Muñoz; P. Castro-Díez; O. Godoy (Biological Invasions, 2014)

B-lymphocyte tolerance and effector function in immunity and autoimmunity - Wasif N. Khan; Jacqueline A. Wright; Eden Kleiman; Justin C. Boucher; Iris Castro; Emily S. Clark (Immunologic Research, 2013)

Fractionation of heavy metals and assessment of contamination of the sediments of Lake Titicaca - Luis Fernando Cáceres Choque; Oswaldo E. Ramos Ramos; Sulema N. Valdez Castro; Rigoberto R. Choque Aspiazu; Rocío G. Choque Mamani; Samuel G. Fernández Alcazar; Ondra Sracek; Prosun Bhattacharya (Environmental Monitoring and Assessment, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Predicting the future climatic suitability for cocoa farming of the world’s leading producer countries, Ghana and Côte d’Ivoire - P. Läderach; A. Martinez-Valle; G. Schroth; N. Castro (Climatic Change, 2013)

Cellular and humoral immune responses of S enegalese sole, S olea senegalensis ( K aup), following challenge with two P hotobacterium damselae subsp. piscicida strains from different geographical origins - B Costas; P C N P Rêgo; I Simões; J F Marques; M Castro‐Cunha; A Afonso (Journal of Fish Diseases, 2013)
The present study aimed to investigate leucocyte responses to inflammation as well as some innate immune parameters of S enegalese sole, S olea senegalensis , following challenge with two strains of P hotobacterium damselae subsp. piscicida belonging to the E uropean and J apanese clones described for this bacterium. Pathogenicity assays were performed to assess the virulence of each P hotobacterium damselae subsp. piscicida strain for sole. Subsequently, fish were intraperitoneally injected with phosphate‐buffered saline (control) or two concentrations (2 × 10 2 and 2 × 10 6 CFU mL −1 ) of each bacterial strain and sampled after 6 and 24 h. Results showed that the E uropean isolate induces a higher degree of response than the J apanese strain. While blood neutrophilia and monocytosis correlated well with the increase in neutrophil and macrophage numbers in the peritoneal cavity, fish infected with the E uropean isolate presented higher peritoneal cell numbers than fish challenged with the J apanese strain. In addition, alternative complement pathway activity and respiratory burst of head kidney leucocytes increased significantly in fish infected with the E uropean isolate. The enhanced innate immune response displayed by S enegalese sole challenged with the E uropean isolate is probably due to the higher degree of virulence presented by this P hotobacterium damselae subsp. piscicida strain.

Western Mediterranean precipitation over the last 300 years from instrumental observations - D. Camuffo; C. Bertolin; N. Diodato; C. Cocheo; M. Barriendos; F. Dominguez-Castro; E. Garnier; M. J. Alcoforado; M. F. Nunes (Climatic Change, 2013)

Differences in nitrogen use strategies between native and exotic tree species: predicting impacts on invaded ecosystems - N. González-Muñoz; P. Castro-Díez; I. M. Parker (Plant and Soil, 2013)

Improving performance of Cytisus striatus on substrates contaminated with hexachlorocyclohexane (HCH) isomers using bacterial inoculants: developing a phytoremediation strategy - C. Becerra-Castro; Á. Prieto-Fernández; P. S. Kidd; N. Weyens; B. Rodríguez-Garrido; M. Touceda-González; M. J. Acea; J. Vangronsveld (Plant and Soil, 2013)

Allele-specific amplification for the detection of ascochyta blight resistance in chickpea - E. Madrid; W. Chen; P. N. Rajesh; P. Castro; T. Millán; J. Gil (Euphytica, 2013)

Score to identify the severity of adult patients with influenza A (H1N1) 2009 virus infection at hospital admission - A. Capelastegui; J. M. Quintana; A. Bilbao; P. P. España; O. Garin; J. Alonso; J. Astray; R. Cantón; J. Castilla; A. Castro; M. Delgado-Rodríguez; P. Godoy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Zebrafish (Danio rerio) life-cycle exposure to chronic low doses of ethinylestradiol modulates p53 gene transcription within the gonads, but not NER pathways - J. Soares; L. Filipe C. Castro; M. A. Reis-Henriques; N. M. Monteiro; M. M. Santos (Ecotoxicology, 2012)

Bioconversion of oleuropein to hydroxytyrosol by lactic acid bacteria - M. M. Santos; C. Piccirillo; P. M. L. Castro; N. Kalogerakis; M. E. Pintado (World Journal of Microbiology and Biotechnology, 2012)

First description of Edwardsiella tarda in Senegalese sole, Solea senegalensis (Kaup) - N Castro; A. E. Toranzo; S. Devesa; A. González; S. Nuñez; B. Magariños (Journal of Fish Diseases, 2012)

Fisheries and trade of seahorses in Brazil: historical perspective, current trends, and future directions - Ierecê L. Rosa; Tacyana P. R. Oliveira; Frederico M. Osório; Luiz E. Moraes; André L. C. Castro; Glaura M. L. Barros; Rômulo R. N. Alves (Biodiversity and Conservation, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Annexin 1 mimetic peptide protects against renal ischemia/reperfusion injury in rats - Fernando N. Facio; Angela A. Sena; Leandro P. Araújo; Gloria E. Mendes; Isac Castro; Marcus A. M. Luz; Luis Yu; Sonia Maria Oliani; Emmanuel A. Burdmann (Journal of Molecular Medicine, 2011)

Eutrophication and macroalgal blooms in temperate and tropical coastal waters: nutrient enrichment experiments with Ulva spp. - MIRTA TEICHBERG; SOPHIA E. FOX; YLVA S. OLSEN; IVAN VALIELA; PAULINA MARTINETTO; OSCAR IRIBARNE; ELIZABETI YURIKO MUTO; MONICA A. V. PETTI; THAÏS N. CORBISIER; MARTÍN SOTO‐JIMÉNEZ; FEDERICO PÁEZ‐OSUNA; PAULA CASTRO; et al. (Global Change Biology, 2010)
Receiving coastal waters and estuaries are among the most nutrient‐enriched environments on earth, and one of the symptoms of the resulting eutrophication is the proliferation of opportunistic, fast‐growing marine seaweeds. Here, we used a widespread macroalga often involved in blooms, Ulva spp., to investigate how supply of nitrogen (N) and phosphorus (P), the two main potential growth‐limiting nutrients, influence macroalgal growth in temperate and tropical coastal waters ranging from low‐ to high‐nutrient supplies. We carried out N and P enrichment field experiments on Ulva spp. in seven coastal systems, with one of these systems represented by three different subestuaries, for a total of nine sites. We showed that rate of growth of Ulva spp. was directly correlated to annual dissolved inorganic nitrogen (DIN) concentrations, where growth increased with increasing DIN concentration. Internal N pools of macroalgal fronds were also linked to increased DIN supply, and algal growth rates were tightly coupled to these internal N pools. The increases in DIN appeared to be related to greater inputs of wastewater to these coastal waters as indicated by high δ 15 N signatures of the algae as DIN increased. N and P enrichment experiments showed that rate of macroalgal growth was controlled by supply of DIN where ambient DIN concentrations were low, and by P where DIN concentrations were higher, regardless of latitude or geographic setting. These results suggest that understanding the basis for macroalgal blooms, and management of these harmful phenomena, will require information as to nutrient sources, and actions to reduce supply of N and P in coastal waters concerned.

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

The western Mediterranean climate: how will it respond to global warming? - Dario Camuffo; C. Bertolin; N. Diodato; M. Barriendos; F. Dominguez-Castro; C. Cocheo; A. della Valle; E. Garnier; M. -J. Alcoforado (Climatic Change, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Downscaling extreme month-long anomalies in southern South America - C. G. Menéndez; M. de Castro; J.-P. Boulanger; A. D’Onofrio; E. Sanchez; A. A. Sörensson; J. Blazquez; A. Elizalde; D. Jacob; H. Le Treut; Z. X. Li; M. N. Núñez; et al. (Climatic Change, 2010)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Effects of exotic invasive trees on nitrogen cycling: a case study in Central Spain - P. Castro-Díez; N. González-Muñoz; A. Alonso; A. Gallardo; L. Poorter (Biological Invasions, 2009)

Relationship Between pH and Stream Water Total Mercury Concentrations in Shenandoah National Park - C. W. Moore; B. J. Cosby; J. N. Galloway; M. S. Castro (Water, Air, & Soil Pollution, 2009)

First isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata (Moreau) - J R López; S Núñez; B Magariños; N Castro; J I Navas; R De La Herran; A E Toranzo (Journal of Fish Diseases, 2009)
The first isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata, is reported. The pathogen was recovered from ulcers of cultured fish, from three different outbreaks. The six isolates obtained were biochemically and serologically characterized and diagnosis was confirmed by polymerase chain reaction using specific primers and partial 16S rRNA gene sequencing. The isolates constituted a homogeneous phenotypic group; however, they belong to two of the different serotypes described within this species. A virulence evaluation of the isolates using Wedge sole fry was also performed.

Biochemical analysis of reactive oxygen species production and antioxidative responses in unripe avocado (Persea americana Mill var Hass) fruits in response to wounding - E. Castro-Mercado; Y. Martinez-Diaz; N. Roman-Tehandon; E. Garcia-Pineda (Protoplasma, 2009)

Molecular epidemiology of hepatitis B virus in an isolated Afro-Brazilian community - A. R. C. Motta-Castro; R. M. B. Martins; N. M. Araujo; C. Niel; G. B. Facholi; B. V. Lago; F. C. A. Mello; S. A. Gomes (Archives of Virology, 2008)

Detection of the yellow‐head virus (YHV) in wild blue shrimp, Penaeus stylirostris , from the Gulf of California and its experimental transmission to the Pacific white shrimp, Penaeus vannamei - R Castro‐Longoria; N Quintero‐Arredondo; J M Grijalva‐Chon; J Ramos‐Paredes (Journal of Fish Diseases, 2008)

A Fluorescent and Phosphorescent Nanoporous Solid: Crystalline Calix[4]arene - Issam Oueslati; Anthony W. Coleman; Baltazar de Castro; Mário N. Berberan-Santos (Journal of Fluorescence, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Characterization of Edwardsiella tarda strains isolated from turbot, Psetta maxima (L.) - N Castro; A E Toranzo; J L Barja; S Núñez; B Magariños (Journal of Fish Diseases, 2006)
The biochemical, serological and molecular characteristics of a group of 21 Edwardsiella tarda strains isolated from turbot, Psetta maxima , in two different areas of Europe were analysed and compared with a total of 13 strains of this bacterial species with different geographical and host origins. All the turbot isolates were biochemically identical to the E. tarda strains included as reference. The use of different techniques including microagglutination, dot blot and Western blot of lipopolysaccharides allowed us to determine that all the turbot isolates constitute an homogeneous and distinctive serological group. Genetic analysis by randomly amplified polymorphic DNA (RAPD) analysis demonstrated that although the E. tarda strains from turbot were compiled in a unique group using the primers P3 and P6, two clonal lineages could be detected when oligonucleotides P4 and P5 were employed.

Oxidation of ethanol to acetaldehyde and free radicals by rat testicular microsomes - Leandro N. Quintans; Gerardo D. Castro; Jos A. Castro (Archives of Toxicology, 2005)

Decline in Assayable Progesterone in Bovine Serum under Different Storage Conditions - T. de Castro; L. Valdez; M. Rodriguez; N. Benquet; E. Rubianes (Tropical Animal Health and Production, 2004)

Structural localization of Al 3+ ions in aluminosilicates: application of heteronuclear chemical shift correlation to 2:1 phyllosilicates - M. D. Alba; M. A. Castro; M. Naranjo; A. C. Perdign (Physics and Chemistry of Minerals, 2004)

Input-Output Budgets of Inorganic Nitrogen for 24 Forest Watersheds in the Northeastern United States: A Review - John L. Campbell; James W. Hornbeck; Myron J. Mitchell; Mary Beth Adams; Mark S. Castro; Charles T. Driscoll; Jeffrey S. Kahl; James N. Kochenderfer; Gene E. Likens; James A. Lynch; Peter S. Murdoch; Sarah J. Nelson; et al. (Water, Air, & Soil Pollution, 2004)

Accumulation, assembly, and digestibility of amarantin expressed in transgenic tropical maize - Q. Rascón-Cruz; S. Sinagawa-García; J. A. Osuna-Castro; N. Bohorova; O. Paredes-López (Theoretical and Applied Genetics, 2004)

Sequencing and Characterization of Plasmid pUIBI-1 from Bacillus thuringiensis Serovar entomocidus LBIT-113 - Joel E. Lpez-Meza; J. Eleazar Barboza-Corona; M. Cristina Del Rincn-Castro; Jorge E. Ibarra (Current Microbiology, 2003)

Molecular epidemiology of hepatitis B virus in Afro-Venezuelan populations - A. Quintero; D. Martínez; B. Alarcón de Noya; A. Costagliola; L. Urbina; N. González; F. Liprandi; D. Castro de Guerra; F. H. Pujol (Archives of Virology, 2002)

Total Mercury Concentrations in Lakes and Fish of Western Maryland, USA - M. S. Castro; E. N. McLaughlin; S. L. Davis; R. P. Morgan, II (Archives of Environmental Contamination and Toxicology, 2002)

Nosocomial Spread of Hepatitis B Virus in Two Hemodialysis Units, Investigated by Restriction Fragment Length Polymorphism Analysis - L. De Castro; N. M. Araujo; R. R. Sabino; F. Alvarenga; C. F. T. Yoshida; S. A. Gomes (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Effects of Disturbance on Nitrogen Export from Forested Lands of the Chesapeake Bay Watershed - Keith N. Eshleman; Robert H. Gardner; Steven W. Seagle; Nancy M. Castro; Daniel A. Fiscus; James R. Webb; James N. Galloway; Frank A. Deviney; Alan T. Herlihy (Environmental Monitoring and Assessment, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

A high incidence of Shigella -induced arthritis in a primate species: major histocompatibility complex class I molecules associated with resistance and susceptiblity, and their relationship to HLA-B27 - J. A. Urvater; S. N. McAdam; J. H. Loehrke; T. M. Allen; J. L. Moran; T. J. Rowell; S. Rojo; J.A. López de Castro; J. D. Taurog; D. I. Watkins (Immunogenetics, 2000)

Geographical distribution of B chromosomes in the grasshopper Eyprepocnemis plorans, along a river basin, is mainly shaped by non-selective historical events - J. Cabrero; M. D. Lo´pez–Leo´n; R. Go´mez; A. J. Castro; A. Marti´–Alganza; J. P. M. Camacho (Chromosome Research, 1997)

Risk-averse foraging by bananaquits on negative energy budgets - Joseph M. Wunderle; María Santa Castro; N. Fetcher (Behavioral Ecology and Sociobiology, 1987)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

Metabolism of acetaldehyde and Custers effect in the yeast - J. M. Carrascosa; Mara Dolores Viguera; I. Nez de Castro; W. A. Scheffers (Antonie van Leeuwenhoek, 1981)